A Current-Mode TransImpedance Amplifier for Capacitive Sensors - Alessandro Nastro; Andrea De Marcellis; Marco Ferrari; Vittorio Ferrari (Proceedings, 2018)
A Current-Mode (CM) TransImpedance Amplifier (TIA) based on Second Generation Current Conveyors (CCIIs) for capacitive microsensor measurements is presented. The designed electronic interface performs a capacitance-to-voltage conversion using 3 CCIIs and 3 resistors exploiting a synchronous-demodulation technique to improve the overall detection sensitivity and resolution of the system. A CM-TIA solution designed at transistor level in AMS0.35 µm integrated CMOS technology with a power consumption lower than 900 µW is proposed. Experimental results obtained with a board-level prototype show linear behavior of the proposed interface circuit with a resolution up to 34.5 fF and a sensitivity up to 223 mV/nF, confirming the theoretical expectations.